2016
DOI: 10.2147/ott.s95101
|View full text |Cite
|
Sign up to set email alerts
|

Advances in targeted and immunobased therapies for colorectal cancer in the genomic era

Abstract: Targeted therapies require information on specific defective signaling pathways or mutations. Advances in genomic technologies and cell biology have led to identification of new therapeutic targets associated with signal-transduction pathways. Survival times of patients with colorectal cancer (CRC) can be extended with combinations of conventional cytotoxic agents and targeted therapies. Targeting EGFR- and VEGFR-signaling systems has been the major focus for treatment of metastatic CRC. However, there are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 217 publications
(225 reference statements)
0
37
2
Order By: Relevance
“…The standard‐of‐care treatment for mCRC using multiagent chemotherapy is effective at slowing the progress of the disease, but long‐term remissions are rare and the treatment side effects are often significant . This has prompted the development of less toxic targeted therapies for the disease, but progress has been slow . Although anti‐EGFR antibody therapeutics have been approved for the treatment of mCRC for several years, the use of these agents has been personalized by determining which patients should not be treated due to predicted resistance rather than identifying individuals significantly likely to benefit from treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard‐of‐care treatment for mCRC using multiagent chemotherapy is effective at slowing the progress of the disease, but long‐term remissions are rare and the treatment side effects are often significant . This has prompted the development of less toxic targeted therapies for the disease, but progress has been slow . Although anti‐EGFR antibody therapeutics have been approved for the treatment of mCRC for several years, the use of these agents has been personalized by determining which patients should not be treated due to predicted resistance rather than identifying individuals significantly likely to benefit from treatment .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 This has prompted the development of less toxic targeted therapies for the disease, but progress has been slow. [58][59][60][61] Although anti-EGFR antibody therapeutics have been approved for the treatment of mCRC for several years, the use of these agents has been personalized by determining which patients should not be treated due to predicted resistance rather than identifying individuals significantly likely to benefit from treatment. 62 Thus, interest has emerged in finding targeted therapies for which biomarkers can positively predict patient benefit from therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since first discovered in Drosophila melanogaster , the Hh signaling pathway has received extensive attention 17. Massive research has confirmed its contributions in embryonic generation and postembryonic regulation of the development of various organs and tissues, including the patterning, growth, and differentiation in the gastrointestinal tracts 15.…”
Section: Hh Signaling Pathwaymentioning
confidence: 99%
“…Hh signaling pathway has been implicated in the pathogenesis of various human cancers; however, the role of the Hh pathway in CRC remains controversial 6. There are two mechanisms of Hh activation: through Hh ligand-dependent activation or through ligand-independent activation, namely, by loss-of-function mutations in Ptc1 or gain-of-function mutations in the proto-oncogene Smo 7. The Hh pathway is viewed as a cancer-related pathway and a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with metastatic colorectal cancer (mCRC), addition of anti-vascular endothelial growth factor (VEGF) and anti-endothelial growth factor receptor (EGFR) biologic agents to chemotherapy regimens, either in the first or second line, improves overall survival (OS), progression-free survival (PFS), and anti-tumor response compared with chemotherapy alone [13]. However, patients frequently develop resistance and ultimately experience disease progression, highlighting a demand for more therapeutic strategies after failure of standard chemotherapy [4, 5].…”
Section: Introductionmentioning
confidence: 99%